2022
DOI: 10.3390/s22062238
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Metal–Organic Framework: Synthesis, Characterization, and Investigation of Their Application in Electrochemical Biosensors for Biomedical Analysis

Abstract: Many studies have addressed electrochemical biosensors because of their simple synthesis process, adjustability, simplification, manipulation of materials’ compositions and features, and wide ranges of detection of different kinds of biomedical analytes. Performant electrochemical biosensors can be achieved by selecting materials that enable faster electron transfer, larger surface areas, very good electrocatalytic activities, and numerous sites for bioconjugation. Several studies have been conducted on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 128 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…However, these sensors have drawbacks such as low detection limits [ 10 , 11 , 12 ]. Due to excellent electrical and chemical properties, several nanomaterials including metal oxides, nanoparticles, graphene, and carbon nanotubes are frequently used as electrochemical biosensors [ 13 ]. It has also been reported that a combination of two or several nanomaterials as nanocomposites further enhance these properties and are frequently used in biosensing applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these sensors have drawbacks such as low detection limits [ 10 , 11 , 12 ]. Due to excellent electrical and chemical properties, several nanomaterials including metal oxides, nanoparticles, graphene, and carbon nanotubes are frequently used as electrochemical biosensors [ 13 ]. It has also been reported that a combination of two or several nanomaterials as nanocomposites further enhance these properties and are frequently used in biosensing applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biosensor-related research has experienced explosive growth over the last two decades. A biosensor is generally defined as an analytical device that converts a biological response into a quantifiable and processable signal [124]. In most biosensors developed so far, electrochemical detection has been used in one way or another, i.e., amperometric, voltammetric, and impedimetric detection.…”
Section: Development Of Electrochemical Dzn Biosensorsmentioning
confidence: 99%
“…A designable photocatalyst is the key component for converting solar energy to produce hydrogen with desirable efficiency [ 4 , 5 , 6 , 7 ]. Recently, two-dimensional covalent organic frameworks (2D COFs), as well as metal-organic frameworks (MOFs), have emerged as promising materials in hydrogen evolution due to their predictable structures, tunable π-conjugation, high crystallinity, and permanent pore channels [ 8 , 9 , 10 , 11 , 12 ]. The precisely tailored 2D COFs provide a platform to illustrate the structure–property relationships during the hydrogen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%